Sociopolitical development: A history and overview of a black liberatory approach to youth development - Hope, Elan C; Anyiwo, Nkemka; Palmer, Gordon J M; Bañales, Josefina; Smith, Chauncey D (The American psychologist, 2023)
Sociopolitical development (SPD) is the process by which people come to understand structural oppression and develop the capacity to reform and transform society, combat oppression, and achieve liberation. In this article, we honor and recognize the community-based framework building of Dr. Roderick Watts and his colleagues, scholars of African descent who pioneered SPD. First, we describe the history and evolution of SPD as both stage and process models of development rooted in Black liberation psychology. We then highlight several contributions of SPD to psychology research and practice including the relevance of sociocultural factors; the integration of intersectionality, well-being, and healing; and the role of context. Throughout, we share parts of conversations with several pioneering SPD scholars regarding the importance of this framework to both Black psychology and psychology broadly. We conclude with recommendations for how psychologists can integrate SPD into their research and practice, as one way to challenge anti-Black racism and reimagine youth resistance against racism and oppression. (PsycInfo Database Record (c) 2023 APA, all rights reserved).